2017
DOI: 10.1016/j.neuropsychologia.2017.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Children who stutter show reduced action-related activity in the rostral cingulate zone

Abstract: 1Previous studies have indicated that children who stutter show not only speech-related 2 problems, but also wider difficulties in self-control. In this study we test the novel hypothesis 3 that children who stutter may experience difficulties with inhibitory control over voluntary 4 actions. We used functional MRI to compare brain activity between children who stutter and 5 children who do not stutter in a task that captures key cognitive aspects of voluntary action 6 control. Participants performed a rolling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 36 publications
2
12
0
Order By: Relevance
“…In other words, if an external sound signals that a motor response needs to be interrupted, CWS are as fast as CWNS to react to this signal. This result seems to challenge two recent contradicting findings of both decreased SSRT in CWS (Harrewijn et al, 2017) and increased SSRT adults who stutter (Markett et al, 2016). Harrewijn et al studied a group of 9 to 14-year-olds.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…In other words, if an external sound signals that a motor response needs to be interrupted, CWS are as fast as CWNS to react to this signal. This result seems to challenge two recent contradicting findings of both decreased SSRT in CWS (Harrewijn et al, 2017) and increased SSRT adults who stutter (Markett et al, 2016). Harrewijn et al studied a group of 9 to 14-year-olds.…”
Section: Discussionmentioning
confidence: 73%
“…Taken together, current findings and the different and sometimes seemingly conflicting findings on response inhibition in people who stutter (Eggers et al, 2010(Eggers et al, , 2013Embrechts et al, 2001;Harrewijn et al, 2017;Markott et al, 2016) necessitate further behavioral and imaging research into the possible role of response inhibition in stuttering.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Of these eight studies, four studies reported that CWS have weaker inhibition skills than CWNS, 3033 three studies revealed that CWS and CWNS have similar inhibition skills, 3436 and one study found that CWS have stronger inhibition skills than CWNS. 37 Thus, the findings from these studies are inconclusive and contradictory as to whether CWS have more difficulty than CWNS suppressing prepotent responses.…”
Section: The Inhibition Skills Of Cwsmentioning
confidence: 96%
“…Out of 36 potential studies, 11 conformed to all inclusion criteria (Supplementary Table 1; De Nil et al, 2000;Stager et al, 2003;Preibisch et al, 2003;De Nil et al, 2008;Watkins et al, 2008;Chang et al, 2009;Ingham et al, 2012;Liu et al, 2014;Lu et al, 2016;Harrewijn et al, 2017;Yang et al, 2017). The studies comprised of 20 different experiments, with 430 total participants (214 cases and 216 controls; smallest sample size of a single study was 26, with an average of 39 subjects per study across all 20 experiments).…”
Section: Meta-analysis For Regions Of Interest Identificationmentioning
confidence: 99%